Characterization of an AFFF impacted freshwater environment using total fluorine, extractable organofluorine and suspect per- and polyfluoroalkyl substance screening analysis. (August 2021) - Koch, Alina; Yukioka, Satoru; Tanaka, Shuhei; Yeung, Leo W.Y.; Kärrman, Anna; Wang, Thanh
Abstract: The vast number of per- and polyfluoroalkyl substances (PFASs) that are in global commerce (n > 4700) pose immense challenges for environmental monitoring. The large discrepancy between this large number and the few PFASs usually monitored suggest that environmental exposure might be substantially underestimated. This study applied a workflow, which included analysis of total fluorine (TF), extractable organofluorine (EOF), 24 target PFASs and suspect screening. The workflow aimed to close the organofluorine mass balance and to tentatively identify overlooked PFASs in various matrices from an aqueous film forming foam (AFFF) contaminated pond and its adjacent riparian zone. PFAS target analysis revealed that water, aquatic invertebrates as well as emergent aquatic insects had high concentrations with up to 2870 ng L −1, 9230 ng g −1 dry weight (dw) and 1470 ng g −1 dw ∑24 PFASs, respectively. The EOF mass balance could be explained by target PFAS analysis for most biota samples such as aquatic invertebrates, emergent aquatic insects and terrestrial spiders and earthworms (i.e. EOF ≈ ∑24 PFASs). In the pond surface water, 42–58% of the EOF was not explained by target PFASs. However most new tentatively identified PFASs ( n = 25) were detected in water, which could contribute to the unknown EOF. Nine suspects could be further identified, which where perfluoroalkyl sulfonamide-based compounds and derivatives that all have been found in historical AFFFs produced by electrochemical fluorination. One suspect, F5S-PFOS, was also detected for the first time in aquatic and terrestrial invertebrates. Highlights: Organofluorine (EOF), PFAS target and suspect screening analysis were combined. Aquatic and terrestrial invertebrates from an AFFF impacted pond were analyzed. For most biota ∑PFAS ≈ EOF concentrations. Most newly identified PFASs ( n = 25) found in water samples. F5S-PFOS was detected for the first time in invertebrates.